Enhancing Marketing Performance Through Entrepreneurial Innovation, Relational Capabilities and Value Co-creation - Marisa Yunita Br Depari (International Journal of Scientific Multidisciplinary Research, 2023)
An examination of an empirical investigation was done to determine how relationship capabilities, value co-creation, and entrepreneurial innovativeness oriented marketing may improve the performance of SME (Small and Medium Enterprise) apparel fashion sectors in Medan, Indonesia. 150 respondents were used in the purposive sampling strategy for data collection. A questionnaire that was distributed directly to the respondents was used to gather the data. Structural Equation Modelling (SEM), with help from the AMOS tool, was used for the data analysis. This essay evaluates three marketing variables that can affect marketing performance